2016
DOI: 10.1038/srep37115
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin associated SETD3 negatively regulates VEGF expression

Abstract: SETD3 is a member of the protein lysine methyltransferase (PKMT) family, which catalyzes the addition of methyl group to lysine residues. Accumulating data suggest that PKMTs are involved in the regulation of a broad spectrum of biological processes by targeting histone and non-histone proteins. Using a proteomic approach, we have identified 172 new SETD3 interacting proteins. We show that SETD3 binds and methylates the transcription factor FoxM1, which has been previously shown to be associated with the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 45 publications
(50 reference statements)
2
37
0
Order By: Relevance
“…7). Our study could, therefore, confirm the observation of Cohn et al that SETD3 regulates the expression of FoxM1 21 . Nevertheless, the discrepancy that we observed in our Kaplan-Meier analysis where the SETD3 expression correlates with a good prognosis while FOXM1 with a bad prognosis in patients with ER-positive tumors could be due to the following reasons: 1) the expression of FOXM1 (up-or down-regulation) is not only regulated by SETD3 but is also regulated by a wide range of factors such as c-Myc, H-Ras, N-Ras, EGFR (epidermal growth factor receptor), ErbB1, HER2/Neu (ErbB2), Notch1, STAT3 (signal transducer and activator of transcription 3), KLF4, GATA3, and others 59 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…7). Our study could, therefore, confirm the observation of Cohn et al that SETD3 regulates the expression of FoxM1 21 . Nevertheless, the discrepancy that we observed in our Kaplan-Meier analysis where the SETD3 expression correlates with a good prognosis while FOXM1 with a bad prognosis in patients with ER-positive tumors could be due to the following reasons: 1) the expression of FOXM1 (up-or down-regulation) is not only regulated by SETD3 but is also regulated by a wide range of factors such as c-Myc, H-Ras, N-Ras, EGFR (epidermal growth factor receptor), ErbB1, HER2/Neu (ErbB2), Notch1, STAT3 (signal transducer and activator of transcription 3), KLF4, GATA3, and others 59 .…”
Section: Discussionsupporting
confidence: 93%
“…According to our and other studies, it seems that SETD3 significantly regulates mechanisms associated with actin regulation, however, the protein network in which SETD3 is involved is unknown. Cohn et al demonstrated that SETD3 can interact with 172 novel proteins such as transcription factors of which FoxM1 was one of them 21 . Also, SETD3 methylates FoxM1 and negatively regulates the expression of Vascular Endothelial Growth Factor (VEGF) under normoxia conditions 21 , a known factor related to angiogenesis and tumor progression 58 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, SET7 associates with GATA1 to promote VEGFA transcription and breast tumor angiogenesis [125]. However, by using ProtoArray system, Cohn et al identified 172 new SETD3 interacting proteins, and further investigation found that SETD3 binds and methylates the transcription factor FoxM1 to inhibit VEGFA expression under hypoxia [126]. In addition, GSK126, an EZH2 inhibitor, inhibits gastric cancer and lung adenocarcinoma cell migration and angiogenesis in solid tumor cell lines through downregulation of VEGFA expression [127].…”
Section: Histone Methylation In Tumor Angiogenesismentioning
confidence: 99%